Italian recommendations on enzymatic debridement in burn surgery. Issue 2 (March 2021) - Ranno, Rosario; Vestita, Michelangelo; Maggio, Giulio; Verrienti, Pasquale; Melandri, Davide; Orlandi, Catuscia; Perniciaro, Giuseppe; De Angelis, Armando; D'Alessio, Roberto; Mataro, Ilaria; Pagnozzi, Eliana; Alessandro, Giovanni; et al.
Highlights: We present recommendations on its use based on knowledge of expert Italian users. The consensus process involved a multi-phase process based on the Delphi method. The results are "ready to use" recommendations available for enzymatic debridement. Abstract: Introduction: Nexobrid®, a bromelain-based type of enzymatic debridement, has become more prevalent in recent years. We present the recommendations on enzymatic debridement (Nexobrid®)'s role based on the practice knowledge of expert Italian users. Methods: The Italian recommendations, endorsed by SIUST (Italian Society of Burn Surgery), on using enzymatic debridement to remove eschars for burn treatment were defined. The definition followed a process to evaluate the level of agreement (a measure of consensus) among selected experts, representing Italian burn centers, concerning defined clinical aspects of enzymatic debridement. The consensus involved a multi-phase process based on the Delphi method. Results: The consensus panel included experts from Italy with a combined experience of 1068 burn patients treated with enzymatic debridement. At the end of round 3 of the Delphi method, the panel reached 100% consensus on 26 out of 27 statements. The panel achieved full, strong consensus (all respondents strongly agreed on the statement) on 24 out of 27 statements. Discussion: The statements provided by the Italian consensus panel represent a "ready to use" set of recommendations for enzymatic debridement in burn surgery that both draw from and complete the existing scientific literature on the topic. These recommendations are specific to the Italian experience and are neither static nor definitive. As such, they will be updated periodically as further quality evidence becomes available.